(untitled) (Acta Entomologica Serbica, 2015)
Collection data on nine species of whitefly collected in the coastal and central regions of Montenegro during October 2012 are presented. Three species are recorded from Montenegro for the first time: Aleuroclava aucubae (Kuwana), Aleurotuba jelinekii (Frauenfeld) and Bemisia afer (Priesner & Hosny) complex. Two of the species, A. aucubae and B. afer complex were found in Tološi, on Citrus sp. and Laurus nobilis, respectively. Aleurotuba jelinekii was found in Podgorica on Viburnum tinus.